الإشارات العلمية في قصة أصحاب الكهف: دراسة لتفسير مفاتيح الغيب لفخر الدين الرازي: Scientific References in The Story of The Companions of The Cave: a Study of Fakhr al-Din al-Razi's Tafsir Mafātīḥ al-Ghayb - Abdulghani, Naser; Ayad, Nahid; Albshkar, Hajer; Alsayd, Abdulnasir; Aboujanah, Yousuf (STAINI Press, 2024)
The scientific inimitability in the Quran is one of the most significant aspects of contemporary Quranic exegesis that researchers have studied and analyzed. These aspects have roots in traditional exegesis books. Al-Razi’s interpretation stands out as one of the most important commentaries addressing some scientific ideas prevalent in his era (544 AH - 606 AH). Researchers employed the analytical and historical methodologies to examine the scientific references in Al-Razi’s interpretation of the story of the Companions of the Cave. This story is considered one of the manifestations of inimitability in Quranic narratives, highlighting the importance of this interpretation, especially in the context of science and inimitability. Including God’s power in reviving the dead (resurrection), prolonged sleep and its influencing factors, and the concept of awakening from sleep and its connection to the resurrection of the dead. The researchers concluded that Al-Razi utilized the scientific perspectives of his time to serve Quranic interpretation while leaving room for other scientific views to adapt to changes in time and place.